PENGARUH LATIHAN DOT DRILLS DAN SHUTTLE RUN TERHADAP PENINGKATAN KELINCAHAN REAKSI ELAKAN PADA PENCAK SILAT PERSINAS ASAD BANGKALAN - Putra, Freanza Diaz Mahesa; Handayani, Heni Yuli; Hidayatullah, Fajar (Fakultas Ilmu Keolahragaan Unimed, 2024)
This research was conducted to determine whether there was an effect of dot drills and shuttle run training on increasing the Agility of Avoidance Reactions in Pencak Silat Personas Asad Bangkalan. The research was carried out over 8 meetings, this type of research is quasi-experimental research. The research design used was a